Akuntabilitas pada Organisasi Religi; Studi Kasus Masjid-Masjid di Balikpapan, Kalimantan Timur - Yunita Fitria (Faculty of Economics and Business Mulawarman University, 2017)
The study aims to test the accountability of the organization in the mosques located in Balikpapan, Kalimantan Timur. This study uses the concept of accountability mechanisms presented by Ebrahim (2003). Data is collected by interview, observation, field notes and document analysis. The study uses semi-structures interview used to explore the perception of mosque board. This study examines 3 mosque organizations and 15 people became interviewees. An interesting result in the study was informal accountability form in Balikpapan mosque. The study consisted of only a few people interviewed, so the results should be interpreted in context and not generalizable. The limitations of this study were that most mosques coud not show the full financial report due to the confidentiality of their financial statements. These findings illustrated to the government about informal accountability in mosques. Thus, this study provides an overview of other studies to see more about accountability in non-profit organizations.Keywords: Accountability, non profit organization, Balikpapan, mosque